The impacts of traffic-related and woodsmoke particulate matter on measures of cardiovascular health: a HEPA filter intervention study. Issue 6 (20th April 2015) - Kajbafzadeh, Majid; Brauer, Michael; Karlen, Barbara; Carlsten, Chris; van Eeden, Stephan; Allen, Ryan W
Abstract : Background: Combustion-generated fine particulate matter (PM2.5 ) is associated with cardiovascular morbidity. Both traffic-related air pollution and residential wood combustion may be important, but few studies have compared their impacts. Objectives: To assess and compare effects of traffic-related and woodsmoke PM2.5 on endothelial function and systemic inflammation (C reactive protein, interleukin-6 and band cells) among healthy adults in Vancouver, British Columbia, Canada, using high efficiency particulate air (HEPA) filtration to introduce indoor PM2.5 exposure gradients. Methods: We recruited 83 healthy adults from 44 homes in traffic-impacted or woodsmoke-impacted areas to participate in this randomised, single-blind cross-over intervention study. PM2.5 concentrations were measured during two consecutive 7-day periods, one with filtration and the other with 'placebo filtration'. Endothelial function and biomarkers of systematic inflammation were measured at the end of each 7-day period. Results: HEPA filtration was associated with a 40% decrease in indoor PM2.5 concentrations. There was no relationship between PM2.5 exposure and endothelial function. There was evidence of an association between indoor PM2.5 and C reactive protein among those in traffic-impacted locations (42.1% increase in C reactive protein per IQR increase in indoor PM2.5, 95% CI 1.2% to 99.5%), but not among those in woodsmoke-impacted locations. There were no associations with interleukin-6 or band cells. Conclusions: Evidence of an association between C reactive protein and indoor PM2.5 among healthy adults in traffic-impacted areas is consistent with the hypothesis that traffic-related particles, even at relatively low concentrations, play an important role in the cardiovascular effects of the urban PM mixture. Trial registration number: http://www.clinicaltrials.gov (NCT01570062 ).